Belly Woman : Birth, Blood and Ebola: the Untold Story. - Black, Benjamin (Neem Tree Press Limited, 2022)
An eye-opening work of reportage and advocacy, Belly Woman chronicles the inside journey through an unfolding global health crisis and the struggle to save the lives of young mothers.
Keywords: Black, Benjamin Oren.; Hospitals -- Maternity services -- Sierra Leone.; Ebola virus disease -- Sierra Leone.; Pregnant women -- Medical care -- Sierra Leone.; Maladie à virus Ebola -- Sierra Leone.; Femmes enceintes -- Soins médicaux -- Sierra Leone.; Medical.; Women's Health.; HEALTH & FITNESS.; Pregnancy & Childbirth.; Infectious Diseases.; MEDICAL.; Maternity.; Nursing.; Human Rights.; POLITICAL SCIENCE.; Disasters & Disaster Relief.; SOCIAL SCIENCE.; BIOGRAPHY & AUTOBIOGRAPHY.; Ebola virus disease; Hospitals -- Maternity services; Pregnant women -- Medical care; Sierra Leone; Electronic books.